Global Youth in A Local Area: Hybridisation of Identity among Young Muslims in Yogyakarta Interfaith Community - Waliyuddin, M. Naufal; Noor, Nina Mariani (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
This article investigates the hybrid portraits of identity among young Muslims who are members of the Young Interfaith Peacemaker Community (YIPC) in Yogyakarta. Several inquiries have articulated that Indonesian youth tend to be dragged into ‘conservative turn’ and extremism ideology. However, in this qualitative research we have found the different faces of young Muslims and, in fact, the behavior and religious expression of nowadays youth are not singular and that simple. By using an interpretive phenomenological approach—and through observation, interviews, and documentation particularly from informants—we formulate an argument that young Muslims in the Yogyakarta interfaith community represent a form of multi-identity amalgamation (hybrid). As part of a globally networked society in a local area, they choose to take a dissimilar path from conservative currents and extremist tendencies and then decide to narrate inclusive values, tolerance, and peace education. These snapshots depict a fusion of their thought or horizon (micro-individual) with the community atmosphere (meso-community) and the reality (macro-social politics) around them—which be called Horizontverschmelzung in Hans-Georg Gadamer’s concept. This could be discovered from a sequence of socio-religious behaviour and expressions among youth who are active in the interfaith community in Yogyakarta.